Pengaruh Pendidikan Kesehatan Tentang HIV/AIDS Pada Kelompok Resiko Tinggi Terhadap Kemauan Mengikuti Program Voluntary Counseling and Testing (VCT) di Wilayah Kota Palopo Sulawesi Selatan - Sriwahyuni Sriwahyuni; Lindriani Lindriani (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To determine the effect of providing health education about HIV / AIDS on the willingness to conduct VCT in high-risk groups in the Palopo City Region of South Sulawesi. Method: This research is a quasi-experimental study, with one group posttest only design. Variables that will be examined include the level of knowledge about HIV / AIDS, and the willingness to do VCT. The sampling technique used is snowball sampling. High-risk groups taken as respondents in this study were sexual offenders, namely sex workers, transsexuals, gays, and pregnant women, drivers and syringe users. With a total of 42 respondents, data analysis used the wilcoxon test. Results: There was a difference in the level of knowledge between before and after getting health education in the Palopo City Region of South Sulawesi in 2019 with the results of statistical tests with p-value =, 013 <, 05. So there is an influence between knowledge about HIV / AIDS and VCT with the willingness of respondents to do VCT in the Palopo City Region of South Sulawesi in 2019. With the results of statistical tests with p-value = .001 <.05. Conclusion: There is a difference in the level of knowledge between before and after getting health education about HIV / AIDS so that there is an influence between the knowledge about HIV / AIDS and VCT with the willingness of respondents to do VCT in Palopo, South Sulawesi.